2021
DOI: 10.1002/cpz1.256
|View full text |Cite
|
Sign up to set email alerts
|

Intravital Imaging of Hepatic Blood Biliary Barrier in Live Mice

Abstract: Understanding the kinetics and spatiotemporal interactions of living cells within the tissue environment requires real‐time imaging. The introduction of two‐photon microscopy has substantially boosted the power of live intravital imaging, making it possible to obtain information of individual cells in near‐physiologic conditions within intact tissues nondestructively. Intravital imaging of the liver has proved useful in understanding its 3D structure, function, and dynamic cellular interactions. Recently we ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The method of qLIM is described elsewhere. 22 Texas red-dextran and AF488-P21 antibodies ( Online Supplementary Table S3 ) were administered intravascularly to visualize the blood flow in liver sinusoids and identify senescent cells in SCD (SS) and control (AS) mice, respectively ( Figure 1A , upper panel; Online Supplementary Movies S1 and S2 ). As shown in Figure 1A , P21-positive cells were localized close to the hepatic sinusoids resembling endothelial cell structures, suggestive of endothelial cell senescence.…”
Section: Resultsmentioning
confidence: 99%
“…The method of qLIM is described elsewhere. 22 Texas red-dextran and AF488-P21 antibodies ( Online Supplementary Table S3 ) were administered intravascularly to visualize the blood flow in liver sinusoids and identify senescent cells in SCD (SS) and control (AS) mice, respectively ( Figure 1A , upper panel; Online Supplementary Movies S1 and S2 ). As shown in Figure 1A , P21-positive cells were localized close to the hepatic sinusoids resembling endothelial cell structures, suggestive of endothelial cell senescence.…”
Section: Resultsmentioning
confidence: 99%
“…Intravital microscopy, which allows for the direct visualization of dynamic cellular processes in living subjects, has been useful in studying bile flow kinetics (157). Intravital microscopic study of cholestatic preclinical murine models revealed many of the cellular consequences of cholestasis discussed above, such as the loss of the blood-bile barrier integrity and impaired bile transporter function (158).…”
Section: Advanced Sequencing and Microscopymentioning
confidence: 99%
“…It has been used to study the mechanism of glioblastoma cells in the tumor microenvironment, cellular interactions that contribute to biliary membrane integrity, and fast spatiotemporal cellular dynamics within neural networks. Additionally, it can be used to distinguish tumor-adjacent cancer cells tagged with fluorescent enzymes [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%